2010
DOI: 10.1002/ddrr.90
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and family functioning in spina bifida

Abstract: A developmentally-oriented bio-neuropsychosocial model is introduced to explain variation in family functioning and psychosocial adjustment in youth and young adults with spina bifida (SB). Research on the family functioning and psychosocial adjustment of individuals with SB is reviewed. The findings of past research on families of youth with SB support a resiliencedisruption view of family functioning. That is, the presence of a child with SB disrupts normative family functioning, but many families adapt to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 69 publications
4
92
0
5
Order By: Relevance
“…Research on transition outcomes among young adults with myelomeningocele in the USA is particularly restricted in scope. Guided by the bio-neuropsychosocial model of psychosocial adjustment in emerging adults with myelomeningocele, 29 this study aims to advance understanding of the interrelationships of sex, LOL, and transition outcomes in young adults with myelomeningocele. Our intent was to evaluate central variables that fall under the 'activities and participation' domain of the World Health Organization's International Classification of Functioning, Disability and Health framework 30 (e.g.…”
mentioning
confidence: 99%
“…Research on transition outcomes among young adults with myelomeningocele in the USA is particularly restricted in scope. Guided by the bio-neuropsychosocial model of psychosocial adjustment in emerging adults with myelomeningocele, 29 this study aims to advance understanding of the interrelationships of sex, LOL, and transition outcomes in young adults with myelomeningocele. Our intent was to evaluate central variables that fall under the 'activities and participation' domain of the World Health Organization's International Classification of Functioning, Disability and Health framework 30 (e.g.…”
mentioning
confidence: 99%
“…A possible reason for this result is that spina bifida imposes a condition that limits the ability of a person to be autonomous and participate actively in their development process. Therefore, parental strategies of action have possibly been interfered by the disability condition, such as delay in the acquisition of skills related to autonomy highlighted by Holmbeck and Devine (2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Daves et al (2006) demonstrated that young people with myelomeningocele have a delay from two to five years on the achievements of autonomy when compared to people of the same age. In addition, parents of pre-teen with spina bifida claim that the sons and daughters have difficulty with their self-care, motivational factors and memory (Holmbeck & Devine, 2010).…”
mentioning
confidence: 99%
“…57 Adolescence often increases family stress. 58 Spina bifida affects not only the patient but also his or her siblings, who are subject to stress and feelings of loss, guilt, frustration, and anger. These feelings have consequences for the sibling, for his or her relationship with the child with spina bifida, and for the entire family.…”
Section: Family Supportmentioning
confidence: 99%